S10. IMPAIRMENT OF REALITY TESTING IN INDIVIDUALS AT CLINICAL HIGH-RISK OF PSYCHOSIS. (9th April 2019) - Xu, Lihua; Zhang, TianHong; Tang, Yingying; Cui, Huiru; Wei, Yanyan; Tang, Xiaochen; Wang, Jijun
Abstract: Background: According to the rating of Scale of Psychotic-risk Syndromes (SOPS), 4 score indicates the individual have self-doubts about the positive symptoms, but 5 score illustrates impairment of reality testing to some extent. The aim of this study is to explore the impacts of reality-testing ability on the clinical characteristics and neurocognitive functions of CHR. Methods: CHR individuals with a maximum score of 4 on one or more positive symptoms were classified as reality-testing maintenance (RTM), meanwhile with a maximum score of 5 on one or more positive symptoms were classified as reality-testing impairment (RTI). Of 300 CHR individuals in SHARP team, 140 were RTM and 134 were RTI. The MATRICS Consensus Cognitive Battery (MCCB) was used to assess neurocognitive functions and 2-year follow-up was conducted. Results: There were differences between the two groups of RTM and RTI on various clinical variables (p<0.05), such as P1, P2, P3, P4, N6, D1, D2, G4, the total scores of P and D, GAF_current, and GAF_drop, and on several neurocognitive tests, such as TMT, BACS, HVLT-R, WMS-Ⅲ, and BVMT-R. Pearson's correlation analysis showed that the total score of positive symptoms was related with each clinical variable (p<0.05), but was not related with any neurocognitive test. In addition, Chi-squared test showed that more individuals in RTM group comorbid with other axisⅠmental disorders and more individuals in RTI group were diagnosed as psychosis related disorders at outpatient. At 2-year follow-up node, there were more individuals with treatment refractory in RTI group, and more RTM individuals remitted. Discussion: CHR individuals with impairment of reality testing are probably closer to psychosis.